Carrot Amphorae Production in Germania inferior - Liesen, Bernd (Rei Cretariae Romanae Fautorum Acta, 2022)
During the late 1st and early 2nd centuries, imitations of levantine ‘carrot’ amphorae were produced in Germania inferior. These vessels were found predominantly in military sites along the Rhine frontier. Since the Eastern Mediterranean amphorae served as containers for dried fruit, the same function can be assumed for the reproductions.